From adoption potential to Transformative Learning around Conservation Agriculture. Issue 1 (1st January 2019) - Probst, L.; Ndah, H. T.; Rodrigues, P.; Basch, G.; Coulibaly, K.; Schuler, J.
ABSTRACT: Purpose: To develop a transformative learning process around the potential for innovation of technologies such as Conservation Agriculture. Design/methodology/approach: We applied principles of Transformative Learning and Communicative Action theories to design a learning process structured by the Qualitative Expert Assessment Tool for Conservation Agriculture Adoption in Africa (QAToCA). Elements of the process include: agroecosystem health exploration, stakeholder mapping, innovation timeline, participatory video, the QAToCA exercise, and specifying change promotion. We tested this approach with a group of farmers and experts in Koumbia, Burkina Faso. Findings: The agroecosystem in Koumbia is under demographic, economic, and climatic pressure. Conservation Agriculture has not been successfully integrated into socio-economic realities or implemented beyond a trial scale. The stakeholder mapping showed that dominant economic players and traditional means of communicating are essential to achieve innovation. Past interventions were not coordinated and focused on technical challenges. The participatory videos were rich in contextual information and created process ownership for research participants. The QAToCA provided a structure for lessons learned and suggestions for change. Practical implications: The learning process may be applied to initiate innovation initiatives in an efficient manner. Theoretical implications: The study shows how Transformative Learning and Communicative Action theories can be used for agricultural innovation. It also underlines the need for further work on how to address the implicit superiority of the process initiator and the integration of learning in institutional practice. Originality: Few studies have attempted to design and test learning processes on agricultural innovation based on theories of learning and Communicative Action.